Community structure along the Western Antarctic continental shelf and a latitudinal change in epibenthic faunal abundance assessed by photographic surveys - Grimes, Candace J.; Donnelly, Kyle; Ka, Cheikhouna; Noor, Nusrat; Mahon, Andrew R.; Halanych, Kenneth M. (Frontiers in Marine Science, 2023)
The Southern Ocean’s continental shelf communities harbor high benthic biodiversity. However, most census methods have relied on trawling or dredging rather than direct observation. Benthic photographic and videographic transect surveys serve a key role in characterizing marine communities’ abundance and diversity, and they also provide information on the spatial arrangement of species within a community. To investigate diversity and abundance in Southern Ocean benthic communities, we employed photographic transects during cruises aboard the RVIB Nathanial B. Palmer (November 2012) and the ASRV Laurence M. Gould (February 2013). One kilometer long photographic transects were conducted at 8 sites along 6,000 km of Western Antarctica from the tip of the Antarctic Peninsula to the Ross Sea from which epifaunal echinoderms, tunicates, arthropods, cnidarians, poriferans, and annelids were identified and counted allowing estimations of biodiversity. Our results do not support a latitudinal trend in diversity, but rather a decrease in abundance of macrofaunal individuals at higher latitude sites. All communities sampled on the Western Antarctic shelf were primarily dominated by ophiuroids, pycnogonids, holothuroids, and demosponges. However, the most abundant taxon across all sites was Ophionotus victoriae, followed by the symbiotic partners Iophon sp. (demosponge) and Ophioplinthus spp. (ophiuroid). Data also confirm that the Southern Ocean is composed of discretely unique benthic communities. These results provide critical understanding of the current community structure and diversity serving as a baseline as the Antarctic continental shelf changes due to rising ocean temperatures, climate change, and collapse of large ice sheets.